Respuesta :

The whole equation is multiply my -1.

-2x2 + 5x + 5 = 0

Now multiply it with -1.

-1 (-2x2 + 5x + 5 = 0) and you get:

2x2 - 5x - 5 = 0.

It doesn't matter the answer will be the same.

Using the sign convention rule the equation [tex]\rm -2x^2 +5x + 5= 0[/tex] after changing the sign is transformed as [tex]\rm 2x^2 -5x - 5= 0[/tex].

What is a sign convention?

Sign convention means the rule that is used when the sign is to be changed. It is applicable only when the equation is considered.

Given

[tex]\rm -2x^2 +5x + 5= 0[/tex] is a quadratic equation.

Multiply both sides by (-1). Then we have

[tex]\rm -\ 2 \ x^2 \ + \ 5 \ x \ + \ 5= 0\\\\\rm -1(-2x^2 +5x + 5 )= -1 * 0[/tex]

On simplifying, we have

[tex]\rm (-1)*(-2x^2 )+ (-1)*5x + (-1)*5= (-1)*0[/tex]

We know the sign convention rule

[tex]\rm Negative *Negative =Positive \\\\Negative*Positive = Negative \\\\Negative*Positive =Negative \\\\Positive*Positive =Positive[/tex]

Then the equation will be

[tex]\rm 2x^2-5x -5= 0[/tex]

Thus, the equation [tex]\rm -2x^2 +5x + 5= 0[/tex] after changing the sign is transformed as [tex]\rm 2x^2 -5x - 5= 0[/tex].

More about the sign convention link is given below.

https://brainly.com/question/25934508